The Education Systems of Europe
47 illus., 1 illus. in color. eReference.
Keywords: This updated second edition presents an analytical description of the education systems of all European countries, following common guidelines. These conceptual guidelines consider various criteria concerning presumptions as to the quality of a good education system. One of the book central aims is to explore the paradoxical character of education, i.e. the relationship between universal values and the search for a national identity. The common structure of the different country analyses oriented by crucial problems of education worldwide guides to discover common patterns of European education compared to that of education systems outside Europe, making its reading relevant to educators around the world. The handbook provides many suggestions for further study.